Acute kidney injury in a postpartum woman with paroxysmal nocturnal hemoglobinuria: A case report and literature review. Issue 1 (10th August 2017) - Nishimoto, Masatoshi; Matsui, Masaru; Tsushima, Hideo; Tanabe, Kaori; Tagawa, Miho; Samejima, Ken‐ich; Akai, Yasuhiro; Saito, Yoshihiko
Abstract: Paroxysmal nocturnal hemoglobinuria is a rare clonal hematopoietic stem cell disorder characterized by intravascular hemolysis, hemoglobinuria, and inflammatory thrombotic state. Intravascular hemolysis in paroxysmal nocturnal hemoglobinuria (PNH) can lead to acute and chronic renal injury through hemoglobin‐mediated toxicity. A 32‐year‐old pregnant woman with myelodysplastic syndrome was admitted to our hospital with severe preeclampsia. Shortly after an urgent caesarean section, she became obtunded and showed signs of acute kidney injury (AKI) with anuria, severe intravascular hemolysis, and hypermagnesemia. She was diagnosed with PNH with a positive Ham test and flow cytometry analysis. Renal magnetic resonance imaging revealed decreased signal intensity in the renal cortex due to hemosiderin deposition. Hemodialysis, plasma exchange, and administration of corticosteroids ameliorated her clinical condition and renal function. This case illustrates that careful management is required to prevent postpartum AKI in pregnant women with PNH.